Analisis Kualitas Pelayanan Kinerja Bengkel Berdasarkan Persepsi Pengunjung dengan Metode IPA di Bengkel X - Moh Ririn Rosyidi; Nailul Izzah (Jurnal Optimalisasi, 2022)
Many organizations exist and make different decisions for the purpose of accommodation and compliance with a given administration so that the buyer continues to use a given administration, the vital nature of administration is the general component and nature of a thing or organization that can satisfy an expressed or proposed need. workshop X is located in Jalan Raya Sembayat, Kec. Manyar Kab. Gresik  busy with service administration for buyers and also until now has many clients, but sometimes errors occur in work, this is because the help system is still manual so it becomes wasteful. The X workshop provided is also not ideal for the various services that exist to support customer improvement, therefore a top-down review is needed to provide a surprisingly better improvement using the Importance Performance Analysis method. Then at that time the value of the respondent's level of similarity was 75%, for the IPA value at the level of conformity, which was 91% on the question of the ease of reaching the workshop. Result of the Importance Performance Analysis, obtained quadrant I (Main Priority), namely P20, P4, P2, this shows that the client anticipates a significant level of significance, but the provision of assistance is not optimal so that there needs to be improvements that pay more attention to rules, Quadrant II (Maintain Achievement) in this area i.e. P5, P6, P7, P8, P9, P10, P11, P12, P13, P14, P15, P16, P17, P19, server friendliness in serving clients, which implies that the client have considered the characteristics, Quadrant III (Low Priority), there are two namely P1, P3, it is necessary to improve the attributes of the assistance after focusing on improving the characteristics that are basic needs, such as the neatness of employees' clothes and waiting room support facilities, Quadrant IV (Exaggerated) P18, respondents consider this quality to have a low level of significance but have truly elite exhibits. While the PGCV value is 8.97 with the question of giving the most important discount according to the customer.